Touristification and the Changing of Spaces for Tourism in Canggu Village - Bayu Adhinata; Made Yaya Sawitri (Universitas Pendidikan Ganesha, 2022)
This article discusses the transformation of Canggu Village from a fishing and farmer village into an urban-characterized area with main economic activities based on tourism. The entry of capitalist investors and the government's designation of a tourism area provide more significant opportunities for this change. This study looks at how the transformation of space for the benefit of tourism causes changes in social conditions in public spaces in Canggu Village. This study used a qualitative approach through in-depth interviews with several informants, such as the head of the Canggu Village, the owner of tourism accommodations, and the Canggu farmers. This study indicates that the village of Canggu has experienced touristification marked by the establishment of accommodations built by investors supported by the local government by establishing this village as a tourism area to increase local revenue. The spaces that have changed by supporting tourism activities have ultimately changed the socio-economic order of the community from non-industrial activities to tourism-based economic activities. The new tourism climate in Canggu Village then co-opted the local community, marked by the emergence of accommodation built by the local community, such as villas, homestays, and guesthouses, as part of the changing perspective of the local community towards economic changes in Canggu Village.